Motivation and Success - George Taukeni, Simon (IntechOpen, 2023)
This book is a collection of chapters addressing numerous features of motivation and success. It includes five chapters divided into two sections: "The Lens of Motivation" and "The Lens of Success". The book demonstrates how motivation can breed success with chapters on entrepreneurship, innovation, socio-culturalism and more.